Innovative Applications of AIGC in Television Content Generation - Huang, Siyang; Wu, Siyu (Transactions on Social Science, Education and Humanities Research, 2024)
Artificial Intelligence and Generative Computing (AIGC) technologies have revolutionized television content generation by enabling automated processes that were previously labor-intensive and time-consuming. This paper explores the innovative applications of AIGC in the broadcast television sector, focusing on three key areas: automated script generation, creation of virtual hosts and actors, and automated video editing. Through case studies and empirical analysis, we examine the effectiveness and impact of these technologies on content quality, production efficiency, and audience engagement. Despite significant advancements, challenges such as ethical considerations and technological limitations persist. Looking forward, the integration of AIGC promises continued advancements in transforming the landscape of television content creation.